APLIKASI PENDEKATAN KESEIMBANGAN PORTOFOLIO ANALISIS NILAI TAMBAH DAN ELASTISITAS KESEMPATAN KERJA PADA INDUSTRI KECIL PENGERINGAN DAN PENGOLAHANIKAN DI KOTA PADANG - Ariusni Ariusni (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2016)
The purpose of this study is to determine (a). The value of the cost and the revenue, (b). The added value and (c). Employment elasticity value of the fish processing industry in the city of Padang. The analysis tool used is multiple linear regression and also use Hayami method. Our research found that there is significant and positive production capacity to value added in industrial dryingband processing fish in Padang. Variable value raw materials to value added in industrial drying and processing fish in Padang significant and positive impact. The variable amount of labor to value added in industrial drying and processing fish in the city of Padang was not significant and positive impact. Variable selling price to value added in industrial drying and processing fish in Padang positive and significant effect. Variable labor costs to value added in industrial drying and processing fish in the city of Padang was not significant and negative effect. Other variable costs to value added in industrial drying and processing fish in Padang significant and negative effect. While the average yield added value there at 30 industrial drying and processing fish in Padang is very large, amounting to Rp. 78,445,203 and an average elasticity of labor in fish drying and processing industry in the city of Padang is inelastic at 0.2093.Keywords : value added, Elasticity, Industry, employment